Is there additional effect of MTHFR C677T mutation on lipid abnormalities in renal allograft recipients? - (:unkn) unknown (ELSEVIER SCIENCE INC, 2003)
Background. The MTHFR C677T mutation and elevated atherogenic lipoprotein levels are known as cardiovascular risk factors in patients with renal transplantation treated with cyclosporine (CsA). The aim of the present study was to evaluate the contribution of MTHFR C677T mutation to the risk of dyslipidemia in renal transplant recipients. We also studied the effect of the MTHFR-C677 T genotype on transplant survival. Methods. The study included 29 nondiabetic renal transplant recipients and 27 healthy controls. MTHFR C677T genotypes were determined by PCR and RFLP techniques. Biochemical parameters were measured in a computerized autoanalyzer. Results. In the patient group, the distribution of the CC, CT, and TT genotypes was 44.8% (n = 13), 37.9% (n = 11), and 17.2% (n = 5), respectively. The frequencies of the C and T alleles were 0.64 and 0.36, respectively. Subjects with the T allele had the highest levels of TC (P < .05) and LDL-C (P < .05); subjects with the CC genotype had the lowest. Conclusion. We observed that the MTHFR T allele has an unfavorable effect on serum lipid profile, leading to a rise in the total and LDL cholesterol concentrations. Thus, we believe that MTHFR C allele has a protective effect and MTHFR T allele has a detrimental effect on the serum lipid profile.
Keywords: PLASMA HOMOCYSTEINE LEVELS; RISK-FACTOR; METHYLENETETRAHYDROFOLATE-REDUCTASE; CARDIOVASCULAR-DISEASE; VASCULAR-DISEASE; MTHFR; TRANSPLANTATION; HYPERLIPIDEMIA; CYCLOSPORINE; VARIANT